The Cambridge handbook of biolinguistics - Boeckx, Cedric; Grohmann, Kleanthes K.; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
Biolinguistics involves the study of language from a broad perspective that embraces natural sciences, helping us better to understand the fundamentals of the faculty of language. This Handbook offers the most comprehensive state-of-the-field survey of the subject available. A team of prominent scholars working in a variety of disciplines is brought together to examine language development, language evolution and neuroscience, as well as providing overviews of the conceptual landscape of the field. The Handbook includes work at the forefront of contemporary research devoted to the evidence for a language instinct, the critical period hypothesis, grammatical maturation, bilingualism, the relation between mind and brain and the role of natural selection in language evolution. It will be welcomed by graduate students and researchers in a wide range of disciplines, including linguistics, evolutionary biology and cognitive science.
Introducing the volume / Kleanthes K. Grohmann and Cedric Boeckx -- Biolinguistics: a historical perspective / Lyle Jenkins -- Biolinguistics yesterday, today and tomorrow / Massimo Piattelli-Palmarini -- The philosophical foundations of biolinguistics / James McGilvray -- Language development, (evidence for) the language instinct / Ianthi Maria Tsimpli -- Sensitive phases in successive language acquisition: the critical period hypothesis revisited / Jurgen M. Meisel -- Discovering word forms and word meanings: the role of phrasal prosody and function words / Severine Millotte, Elodie Cauvet, Perrine Brusini, and Anne Christophe -- Luria's biolinguistic suggestion and the growth of language / Ken Wexler -- Parameters in language acquisition / Lisa Pearl and Jeffrey Lidz -- Bilingualism beyond language: on the impact of bilingualism on executive control / Mireia Hernandez, Clara D. Martin, Nuria Sebastian-Galles, and Albert Costa -- Mind, brain, behavior: the role of experimental syntax in an integrated cognitive science of language / Jon Sprouse and Diogo Almeida -- Working memory and language processing: theory, data and directions for future research / Matthew W. Wagers and Brian McElree -- Computational primitives in phonology and their neural correlates / Philip J. Monahan, Ellen F. Lau, and William J. Idsardi -- Computational primitives in syntax and possible brain correlates / Matthias Schlesewsky and Ina Bornkessel-Schlesewsky -- Computational primitives in morphology and possible brain correlates / Ina Bornkessel-Schlesewsky and Matthias Schlesewsky -- Grounding the cognitive neuroscience of semantics in linguistic theory / Liina Pylkkanen, Jonathan Brennan, and Douglas Bemis -- Modularity and descent with modification / Gary F. Marcus, Cristina D. Rabaglia, and Hugh Rabagliati -- The role of Broca's Area in language function / Gregory Hickok -- Lexical retrieval and breakdown in aphasia and developmental language impairment / Naama Friedmann, Michal Biran, and Dror Dotan -- Genetics of language: roots of specific language deficits / Antonio Benitez-Burraco -- Language evolution: The cognitive capacities of non-human primates / Klaus Zuberbuhler -- Birdsong for biolinguistics / Kazuo Okanoya -- Language, culture and computation: an adaptive systems approach to biolinguistics / Simon Kirby -- Language and natural selection / Derek Bickerton -- The fossils of language: What are they? Who has them? How did they evolve? / Sergio Balari, Antonio Benitez-Burraco, Victor M. Longa, and Guillermo Lorenzo.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Biolinguistics; Neurolinguistics; Language and languages -- Origin; Electronic books